Isothiourea-Catalysed Sequential Kinetic Resolution of Acyclic (±)-1,2-Diols - Harrer, Siegfried; Greenhalgh, Mark D.; Neyyappadath, Rifahath M.; Smith, Andrew D. (Synlett, 2019)
The isothiourea-catalysed acylative kinetic resolution of a range of acyclic (±)-1,2-diols using 1 mol% of catalyst under operationally simple conditions is reported. Significantly, the bifunctional nature of (±)-1,2-diols was exploited in a sequential double kinetic resolution, in which both kinetic resolutions operate synergistically to provide access to highly enantioenriched products. The principles that underpin this process are discussed, and selectivity factors for the individual kinetic resolution steps are reported in a model system.
Keywords: kinetic resolution; isothiourea; 1,2-diols; enantioselectivity; acylation